Hyperthermia-enhanced targeted drug delivery using magnetic resonance-guided focussed ultrasound: a pre-clinical study in a genetic model of pancreatic cancer. (3rd April 2018) - Farr, Navid; Wang, Yak-Nam; D'Andrea, Samantha; Starr, Frank; Partanen, Ari; Gravelle, Kayla M.; McCune, Jeannine S.; Risler, Linda J.; Whang, Stella G.; Chang, Amy; Hingorani, Sunil R.; Lee, Donghoon; et al.
Abstract: Purpose: The lack of effective treatment options for pancreatic cancer has led to a 5-year survival rate of just 8%. Here, we evaluate the ability to enhance targeted drug delivery using mild hyperthermia in combination with the systemic administration of a low-temperature sensitive liposomal formulation of doxorubicin (LTSL-Dox) using a relevant model for pancreas cancer. Materials and methods: Experiments were performed in a genetically engineered mouse model of pancreatic cancer (KPC mice: LSL-Kras G12D/+ ; LSL-Trp53 R172H/+ ; Pdx-1-Cre). LTSL-Dox or free doxorubicin (Dox) was administered via a tail vein catheter. A clinical magnetic resonance-guided high intensity focussed ultrasound (MR-HIFU) system was used to plan treatment, apply the HIFU-induce hyperthermia and monitor therapy. Post-therapy, total Dox concentration in tumour tissue was determined by HPLC and confirmed with fluorescence microscopy. Results: Localized hyperthermia was successfully applied and monitored with a clinical MR-HIFU system. The mild hyperthermia heating algorithm administered by the MR-HIFU system resulted in homogenous heating within the region of interest. MR-HIFU, in combination with LTSL-Dox, resulted in a 23-fold increase in the localised drug concentration and nuclear uptake of doxorubicin within the tumour tissue of KPC mice compared to LTSL-Dox alone. Hyperthermia, in combination with free Dox, resulted in a 2-fold increase compared to Dox alone. Conclusion: This study demonstrates that HIFU-induced hyperthermia in combination with LTSL-Dox can be a non-invasive and effective method in enhancing the localised delivery and penetration of doxorubicin into pancreatic tumours.